The use of augmented reality-based learning media to develop the technology literacy of chemistry teachers in the 21st century - Astuti, Andari Puji; Mawarsari, Venissa Dian; Purnomo, Hindriyanto; Sediyono, Eko (AIP conference proceedings, 2020)
The 21st century chemistry learning process requires teachers to implement creative learning methods that are supported by technology. However, the teachers’ ability to use technology in chemistry learning is still low. The purpose of this study was to develop the teachers’ technology literacy using augmented reality-based learning media. This research used mix-method with sequential strategies of mixed methods. The first stage of this research was conducted by surveying the use of technology in chemistry learning. The instrument used was closed and open questionnaire. The second stage was carried out by collecting qualitative data through interview techniques. The data taken from this stage were to obtain the data of teachers’ technology literacy after they received a training treatment using Augmented Reality based learning media. The research subjects consisted of 25 Chemistry teachers spread in Central Java. The results of the study show that teachers’ literacy in chemistry learning is still low. The training of augmented reality-based learning increases the teachers’ technology literacy. In addition, augmented reality-based learning media also assist teachers to introduce abstract concepts to students. In addition, this learning media also help teachers who have limited tools and materials in the laboratory to introduce the laboratory work virtually to the students.